2012
DOI: 10.1194/jlr.p025536
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for regulated monoacylglycerol acyltransferase expression and activity in human liver

Abstract: Obesity is associated with nonalcoholic fatty liver disease (NAFLD), which represents a spectrum of liver abnormalities that are characterized by an increase in intrahepatic triacylglycerol (TAG) content (i.e., steatosis) with or without infl ammation and fi brosis (i.e., steatohepatitis). The presence of steatosis is an important marker of metabolic dysfunction and correlates closely with multiorgan insulin resistance and dyslipidemia ( 1 ), which are key risk factors for diabetes and coronary artery disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
100
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 32 publications
7
100
0
Order By: Relevance
“…The finding that MGAT1 mRNA levels were increased in the PNPLA3 I148M transgenic mice is consistent with this possibility. Humans with NAFLD have recently been reported to have increased hepatic MGAT activity (51) Levels of mRNA encoding the lipid droplet-associated protein CIDEC, which were increased in the livers of PNPLA3 I148M transgenic mice, are also upregulated in other mouse models of fatty liver disease (52,53). Expression CIDEC is associated with an increase in the size of cytosolic lipid droplets in various cell types (53).…”
Section: Figurementioning
confidence: 96%
“…The finding that MGAT1 mRNA levels were increased in the PNPLA3 I148M transgenic mice is consistent with this possibility. Humans with NAFLD have recently been reported to have increased hepatic MGAT activity (51) Levels of mRNA encoding the lipid droplet-associated protein CIDEC, which were increased in the livers of PNPLA3 I148M transgenic mice, are also upregulated in other mouse models of fatty liver disease (52,53). Expression CIDEC is associated with an increase in the size of cytosolic lipid droplets in various cell types (53).…”
Section: Figurementioning
confidence: 96%
“…MGAT activity in human liver is substantial (10), and MGAT expression is strikingly increased in NAFLD (10 -13). Previous work using antisense oligonucleotides (ASOs) and RNAi approaches have shown that short term hepatic suppression of Mogat1 led to a significant improvement in hepatic insulin signaling and whole-body glucose homeostasis (12,13).…”
mentioning
confidence: 99%
“…Reactions were initiated by incubating microsomal proteins with 4 M [ 14 C]decanoyl-CoA (PerkinElmer Life Sciences) in the presence or absence (control) of 35 M 2-oleoylglycerol in 50 mM HEPES (pH 7.4), 10 mM MgCl 2 , 0.001% Triton X-100, and 2.5% v/v acetone. A non-selective lipase inhibitor MAFP (methyl arachidonyl fluorophosphates) was added to block the hydrolysis of both product and substrate as previously described (24). After 30 min reactions were terminated by adding 50 l of 1% phosphoric acid.…”
Section: Methodsmentioning
confidence: 99%